Influence of 50 Hz electromagnetic fields on recurrent embryogenesis and germination of cork oak somatic embryos - Celestino, Cristina; Picazo, M. L. (Plant cell, tissue and …, 1998)
Plant tissue culture techniques are carried out under environmentally controlled conditions in phytotrons. However, electric components of phytotrons generate electromagnetic ﬁelds that may act as a environmental factor inﬂuencing plant growth and morphogenesis. Isolated somatic embryos of Quercus suber, picked from embryogenic lines, were chronically exposed to a 50 Hz and 15 µT electromagnetic ﬁeld generated in a Helmholtz-coil system for 8 weeks, in order to examine if the extremely low frequency (ELF) magnetic ﬁeld (MF) affected the morphogenic behaviour of embryogenic cultures during recurrent embryogenesis. Germination of somatic embryos from genotype G7.1 was carried out under the same electromagnetic ﬁeld, and also under conditions in which the local geomagnetic ﬁeld was suppressed. The ELF MF did not inﬂuence the growth of embryogenic clumps of the assayed genotypes, but reduced the number of detachable embryos produced by genotype G3.27. The ELF MF did not modify the percentages of germination or plant formation of somatic embryos. However, somatic embryos had better germination when cultured under the suppressed geomagnetic ﬁeld condition.
Keywords: bioelectromagnetism; elf magnetic fields; germination; Quercus Suber L; Somatic embryogenesis; tissue culture

Influence of 50 Hz electromagnetic fields on recurrent embryogenesis and germination of cork oak somatic embryos (Plant cell, tissue and …, 1998)
Plant tissue culture techniques are carried out under environmentally controlled conditions in phytotrons. However, electric components of phytotrons generate electromagnetic ﬁelds that may act as a environmental factor inﬂuencing plant growth and morphogenesis. Isolated somatic embryos of Quercus suber, picked from embryogenic lines, were chronically exposed to a 50 Hz and 15 µT electromagnetic ﬁeld generated in a Helmholtz-coil system for 8 weeks, in order to examine if the extremely low frequency (ELF) magnetic ﬁeld (MF) affected the morphogenic behaviour of embryogenic cultures during recurrent embryogenesis. Germination of somatic embryos from genotype G7.1 was carried out under the same electromagnetic ﬁeld, and also under conditions in which the local geomagnetic ﬁeld was suppressed. The ELF MF did not inﬂuence the growth of embryogenic clumps of the assayed genotypes, but reduced the number of detachable embryos produced by genotype G3.27. The ELF MF did not modify the percentages of germination or plant formation of somatic embryos. However, somatic embryos had better germination when cultured under the suppressed geomagnetic ﬁeld condition.